Analisis Respons Fazlur Rahman terhadap Islamisasi Ilmu Pengetahuan - Ahmad Farid Saifuddin; Kholid Karomi (Fakultas Ushuluddin, Universitas Darussalam Gontor, 2023)
This article aims to analyze the criticism given by Fazlur Rahman on the idea of Islamization of knowledge. According to Rahman, the concept of Islamization was conceptually initiated by SMN al-Attas and has no roots at all. According to Rahman, who is also the starting point for his criticism, first, science is essentially good. This means that it is neutral from all values (value-free). Second, the existence of a variety of views that even differ from one another among Muslim thinkers has an impact on the impossibility of determining which knowledge is Islamic or not. In this paper, the researcher will analyze the argumentative text of Fazlur Rahman's rejection of the Islamization of knowledge based on a conceptual basis about the nature of knowledge. Then the researcher explained the nature of knowledge according to al-Attas. The results of this research are that according to Fazlur Rahman, the problems of modern knowledge lie in a scientist's 'sense of responsibility', not in the concept of knowledge itself. As a result, Fazlur Rahman views that Islamization of knowledge is not necessary. Meanwhile, al-Attas views that the problems of contemporary science lie in knowledge itself. This is because several metaphysical aspects are included in building the concept of knowledge in modern science adopted by philosophers and scientists which cannot be reconciled with the nature of knowledge in Islam. This is where al-Attas sees the need for the Islamization of Contemporary knowledge.